The Influence of Leadership Styles on Gen Z’s Work Performance in the Healthcare Industry within Klang Valley, Malaysia - Nur Izzah Liyana Saari; Hemaloshinee Vasudevan (The Indonesian Institute of Science and Technology Research, 2026)
Effective leadership is essential in the healthcare sector to ensure quality care, strengthen teamwork, and enhance employee engagement, particularly among Generation Z employees. Leadership styles play a crucial role in shaping employee attitudes and performance, while effective human resource management and positive workplace relationships further contribute to productivity. However, challenges such as limited funding, investor pressures, and evolving market trends often drive leaders toward short-term, directive approaches. This study examines the impact of leadership styles on Gen Z work performance in the healthcare sector of Klang Valley, Malaysia. A quantitative approach with a descriptive research design was employed, guided by a deductive method consistent with positivist research philosophy. Data were collected from Gen Z employees working in private healthcare institutions in Klang Valley, a region known for its high concentration of healthcare facilities within Malaysia’s dual-tier system. The study applied judgment sampling to select participants based on relevant criteria. The findings indicate that all proposed hypotheses are supported. Transformational leadership (p < 0.001), transactional leadership (p < 0.001), and situational leadership (p < 0.001) each have a significant positive effect on Gen Z employees’ work performance. These results provide important insights for healthcare organizations to optimize leadership practices and improve workforce outcomes. Aligning leadership strategies with the characteristics and expectations of Gen Z employees can enhance both productivity and engagement, while also contributing to the broader understanding of leadership effectiveness in contemporary healthcare settings.